Model development of ionic-strength-sensitive hydrogel and finite element analysis of gel and dielectrics - Lai, Fukun (2011)
As one of the most important smart hydrogels, the ionic-strength-sensitive hydrogel is increasingly attracting the attention of academic researchers and industrial engineers, due to the wide-range applications in the areas of drug delivery, artificial organ, biomicroelectromechanical (BioMEMS) and so on, resulting from the excellent characteristics, such as controllable swelling/shrinking, sorption capacity, reversible large deformation, good permeability and surface property. So far numerous experimental studies have been carried out for the understanding of the characteristics and mechanism of the ionic-strength-sensitive hydrogel. However, few efforts have been made on the theoretical model development and numerical simulation. In this thesis, a chemo-electro-mechanical model is developed theoretically for simulation of the deformation and chemical as well as electric characteristics of the ionic-strength-sensitive hydrogel, which is termed the Multi-Effect-Coupling Ionic-Strength-Stimulus (MECis) model. The model is capable of modeling the chemical, electric and mechanical fields, where the three sets of the field equations govern the mass conservation, the electric field and the momentum conservation in both the hydrogel and solution domains. Associated with the field governing equations, the three sets of the constitutive laws are also formulated, namely the constitutive flux, the fixed charge equation, and the mechanical material law.